Invitation and information in newspaper as a means of directing young workers to libraries (the methodological solution of experiment) - Rimša, Vytautas (Knygotyra, 1987)
The conception and the model of the experiment dedicated to the intensity of the process of directing young workers to libraries together with other interdepartmental centralized sociological-psychological research problems on the theme “The role of libraries in developing and satisfying professional and spiritual interests of young workers”, was carried out.The experiment was started by using announcement, which was printed in the local newspaper. Tendencies and interaction of communication systems “Newspaper-reader-library” were analized.In Lithuania the research is being carried out in 1981–1985.The research in Lithuania is being carried carried out in 1981 in Vilnius confirmed the correctness of this solution. Series of such experiments were also carried out in 1982 in Kaunas and Panevėžys.